Does Regulatory Supervision Curtail Microfinance Profitability and Outreach? - Cull, Robert; Demirguc-Kunt, Asli; Morduch, Jonathan (2012)
Regulation allows microfinance institutions to take deposits and expand their banking functions, but complying with regulation can be costly. We examine implications for institutions' profitability and their outreach to small-scale borrowers and women, using a newly-constructed dataset on 245 leading institutions. Controlling for the non-random assignment of supervision via treatment effects and instrumental variables regressions, we find evidence consistent with the hypothesis that profit-oriented microfinance institutions respond to supervision by maintaining profit rates but curtailing outreach to women and customers that are costly to reach. Institutions with a weaker commercial focus instead tend to reduce profitability but maintain outreach.